RESISTENSI PEDAGANG KAKI LIMA YANG BERDAGANG DI SEPANJANG JALAN COLOMBO YOGYAKARTA - , NOVITA SURYANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The problem in this study is in the regulation and control of the Colombo Street vendors who have set up in Sleman Regency Regulation No. 11 Year 2004 was met with resistance from street vendors. Resistance along Jalan Colombo against local regulation is referred to as resistance hawkers along Jalan Colombo. This resistance was shown there are many street vendors who sell along Jalan Colombo despite being banned. Based on those problems, the purpose of this research is to examine and analyze (1) the form of resistance hawkers who trade along Jalan Colombo Yogyakarta